2011
DOI: 10.2967/jnumed.110.083956
|View full text |Cite
|
Sign up to set email alerts
|

Total Abdominal 18F-FDG Uptake Reflects Intestinal Adenoma Burden in Apc Mutant Mice

Abstract: Apc mutant (Apc Min ) mice develop multiple adenomas in their intestines and are widely used to study colorectal carcinogenesis and chemopreventive approaches. Molecular imaging of intestinal adenomas could potentially provide noninvasive longitudinal evaluation of these lesions in living mice. Therefore, the aim of this study was to investigate the role of 18 F-FDG PET in the Apc Min mouse model. Methods: Apc Min mice (n 5 8) fed a purified diet were imaged serially after injection of 18 F-FDG at age 9 and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…The findings reported here extend previous work by other investigators who pioneered the application of FDG-PET for studies of de novo tumor development in Tg mouse models of human pancreatic cancer, 46 colon cancer 47 and thymoma, 48 and also encountered problems that limited the scope of their investigations. PET imaging in the pancreatic cancer model was limited to proof-of-principle in terms of tumor detection—no attempt was made to monitor tumor progression in individual mice in a quantitative, objective manner.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The findings reported here extend previous work by other investigators who pioneered the application of FDG-PET for studies of de novo tumor development in Tg mouse models of human pancreatic cancer, 46 colon cancer 47 and thymoma, 48 and also encountered problems that limited the scope of their investigations. PET imaging in the pancreatic cancer model was limited to proof-of-principle in terms of tumor detection—no attempt was made to monitor tumor progression in individual mice in a quantitative, objective manner.…”
Section: Discussionsupporting
confidence: 84%
“…In the colon cancer model, adenomas could only be visualized upon PET imaging ex vivo , as lesion-specific imaging in vivo was not feasible. 47 The study on thymomas was inadvertently handicapped by the anatomic location of the thymus in close proximity to the heart—a tissue with major physiologic uptake of FDG that tends to overwhelm the comparably small changes in metabolic activity (FDG uptake) of nearby tissues. The FDG-PET approach used in the present study has overcome the shortcomings noted above.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, another study of prostate cancer in rats showed that the global FDG SUV might remain unchanged after chemotherapy with gemcitabine; however potential relevance to clinical setting remains to be established (38). Our preliminary results show that tumor FDG uptake decreases with successful chemohormonal treatment, although imaging findings may be discordant with those of other manifestations of disease including changes in the levels of serum PSA or circulating tumor cells (39) (Fig. 2).…”
Section: Assessment Of Treatment Responsesupporting
confidence: 52%
“…2). For example, there may be differences in imaging-based assessment based on the response criteria that is employed in the data analysis such as Response Evaluation Criteria In Solid Tumors (RECIST 1.0 and RECIST 1.1), European Organization for Research and Treatment of Cancer (EORTC), or PET Response Criteria in Solid Tumors (PERCIST) (39). Clearly additional studies will be needed to decipher the optimal combination of relevant data that can most accurately reflect the effect of various current and novel therapies.…”
Section: Assessment Of Treatment Responsementioning
confidence: 99%
“…14, 15, 17 However, preliminary experiments with FDG-PET imaging of acute IVC DVT did not allow thrombus detection due to high FDG background in the kidneys and spine, as well as the surrounding bowel, an organ with high glucose utilization. 19 Therefore we established a new murine stasis-induced DVT model in the jugular vein, an area of lower background FDG uptake and a common site of clinical DVT. 5 Jugular DVT were readily detected as obstructions on CT venography, in contrast to sham-operated contralateral jugular veins ( Fig.…”
Section: Resultsmentioning
confidence: 99%